Age-related penetrance of endocrine tumours in multiple endocrine neoplasia type 1 (MEN1): a multicentre study of 258 gene carriers - Machens, Andreas; Schaaf, Ludwig; Karges, Wolfram; Frank-Raue, Karin; Bartsch, Detlef K.; Rothmund, Matthias; Schneyer, Ulrich; Goretzki, Peter; Raue, Friedhelm; Dralle, Henning (Clinical endocrinology, 2007)
Objective In multiple endocrine neoplasia type 1 (MEN1), age-related tumour penetrance according to the type of MEN1 germline mutation has not been investigated in-depth. This study was conducted to examine whether carriers of out-of-frame/truncating and in-frame MEN1 mutations differ in age-related tumour penetrance. Design A multicentre study with biochemical, hormonal and radiological screening for MEN1-associated tumours. Patients A total of 258 MEN1 carriers from six major German tertiary referral centres averaging 43 years of age at last follow-up. Measurements Main outcome measure was time to first diagnosis of MEN1-associated tumours. Results Independent of the year of birth and observation period, time to first tumour diagnosis did not vary much by the type of MEN1 germline mutation or endocrine organ system, and perhaps not even by the type of endocrine tumour when the amount of time was considered by which the diagnosis probably has been advanced through the manifestation of hormonal symptoms. Parathyroid hyperplasia and adenomas developed almost twice as often as enteropancreatic and pituitary tumours (77%vs. 49-32%), and more than five to sevenfold as often as adrenal cortical tumours and carcinoids (77%vs. 15-10%), reaching penetrance rates of up to 90%, 60%, 40%, 26% and 17%, respectively. The heterogeneity of tumour penetrance was marked, ranging from 9 years to 25 years for the earliest, and from 68 years to 77 years for the latest tumour manifestation. Conclusions Because of our inability of predicting tumour penetrance and malignant transformation individually, life-long follow-up of MEN1 carriers is warranted to prevent tumour morbidity.